Nitrogen and harvesting time on the components of forage and seed yield of guineagrass cultivar ’Mombaça’ - Neto, Armindo Barth; Boleta, Vinícius Scandolara; Pancera Júnior, Edson José; Almeida, Gleice Menezes de; do Canto, Marcos Weber; Gasparino, Eliane; Baltazar, Leonardo Fiorio (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effects of nitrogen doses and harvesting time, on the yield components of forage and seed production of Mombaça Guineagrass (Panicum maximum cultivar Mombaça). The treatments were composed by N doses (0, 75, 150, 225 and 300 kg ha-1) and two harvesting times (8 and 14 days after anthesis). The experimental design was the randomized complete block in a split-plot arrangement with four replicates. Forage and leaf lamina yield were positively and linearly affected by N doses. The characters density of fertile tillers, apparent number of seeds and number of pure seeds per panicle, and apparent and pure seed yields were significantly affected by the interaction between N doses and harvesting time. Positive correlation was observed between apparent or pure seed yield and number of seed per panicle and weight of one thousand seeds. The highest apparent seed yield of 89.1 kg ha-1 and pure seed yield of 28.2 kg ha-1 were observed on nitrogen doses at 241.2 and 250.0 kg ha-1, respectively, at 8 days after anthesis.